Investigação do efeito proliferativo e migratório do peptídeo liberador de gastrina (GRP) sobre uma linhagem de adenocarcinoma pulmonar - Jaeger, Natália (2014)
Lung cancer is the most commonly diagnosed type of cancer and the leading cause of cancer related mortality in the world, causing nearly one million deaths per year. Among all histological types, adenocarcinoma is the most frequent one (75-80%). Gastrin-releasing peptide (GRP) is considered to be a mitogen, capable of inducing cell proliferation, since it is involved in fetal lung development. This neuropeptide had its effect on tumor growth first identified in human cells of small cell lung cancer, acting as an autocrine growth factor for tumor tissues by binding to its receptor GRPR. The receptor has been found in many tumor types such as prostate, breast, stomach, pancreas and colon. Moreover, this peptide acts as a morphogen, in angiogenesis and is related to inflammatory processes and in the regulation of cells of the immune system. Furthermore, asymptomatic smokers have high levels of GRP in bronchoalveolar lavage and urine. However, little is known about its effects in tumorigenesis and metastasis, and which molecular mechanisms and signaling pathways are responsible for the effects found. Our group demonstrated recently that GRP could act as a chemotactic molecule for neutrophils. Thus, we hypothesized that GRP could be also a chemotactic stimulus to tumor cells expressing the GRPR. In this study, we tested this hypothesis by examining the effect of GRP on proliferation, survival and migration of cells from the adenocarcinoma cell line A549, seeking to identify the mechanisms of action of this peptide. These cells express high levels of GRPR and treatment with GRP leads to activation of kinases such as AKT and ERK1/2 that are involved in the cellular processes mentioned. Our results suggest that GRP is a migratory stimulus to these cells without evidence of significant effect on their proliferation or survival to treatment with the chemotherapy drug cisplatin (CDDP). Nonetheless, they become more sensitive to CDDP when the drug is combined with a GRPR antagonist. Thus, we believe that future studies should consider a possible role for GRP in metastasis of NSCLC.